Arizona Water Resource Vol. 21 No. 3 (Summer 2013) - University of Arizona. Water Resources Research Center. (Water Resources Research Center, College of Agriculture, University of Arizona (Tucson, AZ), 2013)
On Saturday, June 1, 2013, water was released from Elephant Butte Reservoir in South Central New Mexico into the Rio Grande. It took more than two days to travel the 80 miles to fields near Las Cruces, as water soaked into the parched riverbed. Waiting for the flow were chile, pecan, cotton and alfalfa growers in Southern New Mexico, Western Texas and Mexico, as well as the city of El Paso, Texas, which depends on the Rio Grande for half its water supply.